The effect of data driven learning on receptive vocabulary knowledge of Yemeni University learners - Asmaa Al-Mahbashi; Noorizah Mohd Noor; Zaini Amir (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Vocabulary is of vital importance for EFL learners particularly for its major contribution to reading comprehension. The lack of necessary support for learning vocabulary effectively explains why EFL university learners still have limited vocabulary knowledge. The integration of computer technology has offered language teachers and learners a variety of tools to assist in developing pedagogical practices and language learning. One of these tools is corpora, also known as data-driven learning (DDL). The purpose of this study is to examine whether DDL instruction has a significant effect on developing EFL Yemeni learners’ words meaning as well as the collocation of receptive vocabulary knowledge compared to the dictionary use. The participants in this study were 60 female second level English language students who were divided into an experimental group (DDL group) and a control group (dictionary group). The findings from the pretest result demonstrated comparability of the two groups in two aspects of vocabulary knowledge. However, the results from the posttest and the delayed posttest showed that the learning outcomes of the DDL group were significantly higher than the dictionary group. The study findings confirmed the substantial short and long term effects of DDL instructional method on vocabulary learning. Based on the study results, there is a great need for raising teachers’ and learners’ awareness of the effectiveness of the DDL method particularly in a Yemeni context where corpus use is still a novel method for learning.